THE INFLUENCE OF TRUST AND RISK ON THE USE OF QRIS WITH FRAUD ISSUES AS A MODERATING VARIABLE IN BANDUNG - Indah Kusprasetya; Budi Rustandi Kartawinata; Aldi Akbar (PT. Jurnal Center Indonesia Publisher, 2026)
The development of digital payment systems has driven the increasing use of the Indonesian Standard Quick Response Code (QRIS) as a practical and integrated cashless transaction method. Although QRIS adoption continues to increase, its continued use is still influenced by trust, perceived risk, and the prevalence of fraud in digital transactions. This study aims to analyze the influence of trust and risk on QRIS use, with fraud as a moderating variable, in the city of Bandung. This study used a quantitative approach with a survey of 200 QRIS user respondents. The data analysis technique used was Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results showed that trust had a positive and significant effect on QRIS use, while risk had a negative and significant effect. Furthermore, fraud moderated the relationship between trust and QRIS use by weakening the influence of trust, and moderated the relationship between risk and QRIS use by strengthening the influence of risk. These findings confirm that although QRIS offers convenience and efficiency, perceptions of risk and fraud remain crucial factors influencing usage behavior. This research is expected to provide theoretical contributions to the development of digital payment technology adoption models and provide practical implications for regulators, payment service providers, and MSMEs in strengthening security, improving digital literacy, and building user trust in the QRIS payment system.